First year student expectations: Results from a university-wide student survey - Crisp, Geoffrey; Palmer, Edward; Turnbull, Deborah; Nettelbeck, Ted; Ward, Lynn; LeCouteur, Amanda; Sarris, Aspa; Strelan, Peter; Schneider, Luke (Journal of University Teaching and Learning Practice, 2009)
Although much has been written on the first-year experience of students at higher education institutions, less attention has been directed to the expectations of students when they enter an institution for the first time. This paper provides additional insights into the expectations of students at an Australian university and highlights areas in which students’ expectations may not necessarily align with the realities of common university practices. By providing opportunities for students to articulate their expectations, staff are able to use the responses for a constructive dialogue and work towards a more positive alignment between perceived expectations and levels of student satisfaction with their experience.